Spiritualisasi dalam Mengatasi Problematika Guru di Pesantren Al-Qodiri 1 Jember dan Pesantren Baitul Arqom Balung Kabupaten Jember - Imron Fauzi (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2018)
Teachers ' professionalism is the mandate of law No. 20-year 2003, Act No. 14 of the year 2005, PP No. 74 years 2008, and Permendiknas No. 16 of the year 2007, yet still many such problamatika the teacher happens, especially related to the qualifications and performance of teachers. However, the spiritualization applied by KH. ACH. Muzakki Shah as caretakers of the Pesantren Al-Qodiri 1 Jember and KH. Masykur Abdul Mu'iad, as caretakers of the Pesantren Baitul Arqom Balung, proved that teachers can address problems through the application of spiritual leadership. In accordance with the nature and character of the issues become the focus in this paper, the study was designed with a qualitative approach, which is used to conduct studies and explorative deskriptive. Conclusion this study i.e. spiritualization at pesantren Al-Qodiri Jember and boarding 1 Baitul Arqom Balung, has a uniqueness for example when teacher recruitment process, there are additional criteria are required, including the following: must have sincerity and motivation (ghirrah) in educating high, has the understanding and practice of Islam is good, has character and personality rather and have communication skills that are helpful and behaving politely. This proves that the teachers, in addition to be able to teach in accordance with his duties well, also being required to implement the values of spirituality in all its activities.